Suppression of savanna ants alters invertebrate composition and influences key ecosystem processes. Issue 6 (1st June 2016) - Parr, C. L.; Eggleton, P.; Davies, A. B.; Evans, T. A.; Holdsworth, S.
Abstract: In almost every ecosystem, ants (Hymenoptera: Formicidae) are the dominant terrestrial invertebrate group. Their functional value was highlighted by Wilson (1987) who famously declared that invertebrates are the "little things that run the world." However, while it is generally accepted that ants fulfil important functions, few studies have tested these assumptions and demonstrated what happens in their absence. We report on a novel large‐scale field experiment in undisturbed savanna habitat where we examined how ants influence the abundance of other invertebrate taxa in the system, and affect the key processes of decomposition and herbivory. Our experiment demonstrated that ants suppressed the abundance and activity of beetles, millipedes, and termites, and also influenced decomposition rates and levels of herbivory. Our study is the first to show that top‐down control of termites by ants can have important ecosystem consequences. Further studies are needed to elucidate the effects ant communities have on other aspects of the ecosystem (e.g., soils, nutrient cycling, the microbial community) and how their relative importance for ecosystem function varies among ecosystem types (e.g., savanna vs. forest).